Implementasi Pembelajaran Biologi Terintegrasi Nilai-Nilai Keislaman Pada Materi Sistem Reproduksi Manusia - Sukmawati Baharung; Izattul Isnaini (PT. Nawa Edukasi Nusantara, 2026)
The integration of Islamic values in biology learning, especially reproductive system material, is a manifestation of eliminating the dichotomy between religious knowledge and general knowledge. The dichotomy or separation between general knowledge and religion is an attempt to implement secular life with a partial, not holistic, perspective. This also aims to ensure that students who receive material about biology learning, especially material about the human reproductive system, can think in a balanced way, both in terms of general Islamic knowledge. In biology learning, Islamic integration can be done using two models, namely using the Al-Qur'an integration model as a source of inspiration and the second using the Al-Qur'an as a source of confirmation. The first model uses the Al-Qur'an as an umbrella of knowledge or a source of inspiration, a reference source which is then explained by biological phenomena. Meanwhile, in the second model, critical analysis or discussion of phenomena in biology is carried out, then confirmed with the Al-Qur'an. In the sense that the findings obtained through science, in this case biology, are to clarify what is in the Al-Qur'an.